PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGEMBANGKAN KECERDASAN EMOSIONAL ANAK DI SMAN 1 TAMBUN SELATAN - Saepulloh, Aep; Asiah, Siti (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2015)
The purpose of this study to determine the role of teachers Islamic education in developing children emotional intelligence and to determine the factors supporting and inhibiting teachers of Islamic education in developing children's emotional intelligence in SMA Negeri 1 Tambun Selatan (South Tambun). In general, the role of teachers of Islamic education in SMAN 1 Tambun Selatan as a motivator, informator, facilitator, inspiration, organizer, initiator, supervisor, manager classes, proofreader, and evaluators have been implemented with some success in developing emotional intelligence of students. But such success is inseparable from the support and the role of other teachers, including schools in the development process. The methods used is the method of teaching the faith and other methods.